THE USE OF SCHOOLOGY AS AN ALTERNATIVE OF LEARNING APPLICATIONS IN THE COVID-19 PANDEMIC PERIOD TO IMPROVE STUDENTS 'WRITING ABILITY - Anggraeni, Anita; Rachmijati, Cynantia (PrimaryEdu : Journal of Primary Education, 2021)
The research objective entitled "Schoology : an alternative of learning applications to improve studentsâ€™ writing skills in the Covid 19â€ to is to determine the effect of Schoology online learning media on students' writing skills and to identify students' perceptions about the use of Schoology. The research method used a descriptive qualitative research. Technique in collecting the data were test, interview,questionnaire with research subject is 44 PGSD Students from Class of 2019. The content analysis method was used to analyze the data that was started from 1)data reduction, 2)data presentation, 3)drawing conclusion and verification. The results showed that 85.59% of students agreed that the use of Schoology improved their English language skills in general and 85.90% of students agreed it improved their writing skills. Perceptions of students using Schoology : 13.42% that Schoology is easy to use, 20.13% of students have an ordinary impression, 65.77% of students have the impression that is difficult to use. From their submitted task, there was improving of 40% of score and lessen writing error found.It is to be concluded that Schoology did improve writing skill because the language of instruction in Schoology was English with user friendly outlook hence force the students to study harder using and writing in English.